The Application Of The Weighted Product (WP) Method To Determine The 1st General Champion In SMT TD Pardede Foundation - Misael F Siahaan; Agustina Simangunsong (Putaka Timur Publisher, 2021)
SMK T.D. Pardede Foundation selects students from each class to get 1st place overall, to increase students' enthusiasm for learning, and students who get 1st place overall will get scholarships for the next 1 semester. The general 1st place selection system at SMK TD Pardede Foundation involves every class. The selection is based on the highest Knowledge Score, with several important values ​​such as Skill Average Score, Extracurricular Value, Attendance Value, and Character Value. So far, determining the overall 1st place winner has not been optimal and is still done manually, in which the selection of the general 1st place winner is still subjective. If viewed from these problems, it is necessary to make a decision support system as a tool to evaluate the potential of students. In this case, 5 criteria are determined, namely Total Knowledge Value, Number of Skills, Extracurricular Value, Attendance Value, and Character Value. and based on the 5 criteria above, the author uses the Weighted Product (WP) method. Using the Weighted Product (WP) method is more efficient because the time used in the calculation is shorter. This method was chosen because it can determine the weight of each attribute. The results of this study have resulted in a Decision Support System to Determine the Web-Based General Champion using the Weighted Product method using 5 variable criteria to determine the overall 1st place winner.